Menginspirasi Peluang Usaha Melalui Komunikasi Lintas Budaya - Misnan Misnan; Agus Hitopa Sukma; Obing Zaid Sobir; Hiswanti Hiswanti; Mayang Riyanti; Iswahyu Pranawukir; Alamsyah Alamsyah (Lembaga Penelitian Dan Pengabdian Pada Masyarakat (LPPM) Institut Bisnis dan Informatika (IBI) Kosgoro 1957, 2020)
The Inter-cultural communication is expected to inspire business opportunities and cross cultural communication. The main objection is the mind set changing of students at SDN Lenteng Agung 11 and IBI Kosgoro 1957 students for their professional career in the future. The other aim is to broaden local horizons into global ones. The inter-cultural communication has strategic potential to inspire Indonesian students to see wider business opportunities with more innovative and creatively. It is expected to lead the entrepreneurship enhancement. The method is counseling with the participatory observation combining. The result showed that the student’s entrepreneurship insight appearanced based on the various professions of Korean guests. The developed, high-income country, Korea rely its economic on private sector. Intercultural communication is expected to inspire Indonesian students to build businesses based on creative ideas based on Korea culture. Through this activity, there is mind set changing and increase business self-confidence among Indonesian students.